Native-state stability determines the extent of degradation relative to secretion of protein variants from Pichia pastoris - Whyteside, Graham; Alcocer, Marcos J.C.; Kumita, Janet R.; Dobson, Christopher M.; Lazarou, Maria; Pleass, Richard J.; Archer, David B. (Public Library of Science, 2011)
We have investigated the relationship between the stability and secreted yield of a series of mutational variants of human lysozyme (HuL) in Pichia pastoris. We show that genes directly involved in the unfolded protein response (UPR), ER-associated degradation (ERAD) and ER-phagy are transcriptionally up-regulated more quickly and to higher levels in response to expression of more highly-destabilised HuL variants and those variants are secreted to lower yield. We also show that the less stable variants are retained within the cell and may also be targeted for degradation. To explore the relationship between stability and secretion further, two different single-chain-variable-fragment (scFv) antibodies were also expressed in P. pastoris, but only one of the scFvs gave rise to secreted protein. The non-secreted scFv was detected within the cell and the UPR indicators were pronounced, as they were for the poorly-secreted HuL variants. The non-secreted scFv was modified by changing either the framework regions or the linker to improve the predicted stability of the scFv and secretion was then achieved and the levels of UPR indicators were lowered Our data support the hypothesis that less stable proteins are targeted for degradation over secretion and that this accounts for the decrease in the yields observed. We discuss the secretion of proteins in relation to lysozyme amyloidosis, in particular, and optimised protein secretion, in general.